Effect of plant ontogeny on yield and chemical constituents of essential oil in Sweet basil (Ocimum basilicum L.) grown in Sudan - Aburigal, Yasmin Adam Ali; Elmogtaba, Elfadl Y.; Mirghani, Mohamed Elwathig Saeed; Sirible, Awatif A. M.; Hamza, Nada; Hussein, Ismail Hassan (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Sweet basil (Ocimum basilicum L.), belonging to family Lamiaceae, is very important for its therapeutic and cosmetic potential. The yield and constituents of essential oils in plants are highly dependent on the harvesting time. This study was carried out to assess the effect of plant ontogeny on essential oil yield and chemical constituents for four sweet basil accessions cultivated under irrigation conditions. The essential oils were hydro-distilled from the leaves harvested during the stages of pre-flowering, at flowering and post-flowering. The chemical constituents were determined by GC-MS. The results reveal that the essential oil content ranged from 0.1% to 0.2% at the pre-flowering stage, whereas the oil content obtained at the post-flowering stage was 0.1% for all investigated accessions. The highest essential oil content was recorded at flowering stage (0.2-0.5%). The two wild Sudanese accessions had the maximum content (0.5%). The major chemical constituents, linalool, citral, methyl eugenol, and eucalyptol reported at different developmental stages, varied between 5.73% and 32.93%.